Carotid Wall Longitudinal Motion in Ultrasound Imaging: An Expert Consensus Review - Rizi, Fereshteh Yousefi; Au, Jason; Yli-Ollila, Heikki; Golemati, Spyretta; Makunaite, Monika; Orkisz, Maciej; Navab, Nassir; Macdonald, Maureen; Laitinen, Tiina Marja; Behnam, Hamid; Gao, Zhifan; Gastounioti, Aimilia; et al. (Ultrasound in Medicine and Biology, 2020)
Motion extracted from the carotid artery wall provides unique information for vascular health evaluation. Carotid artery longitudinal wall motion corresponds to the multiphasic arterial wall excursion in the direction parallel to blood flow during the cardiac cycle. While this motion phenomenon has been well characterized, there is a general lack of awareness regarding its implications for vascular health assessment or even basic vascular physiology. In the last decade, novel estimation strategies and clinical investigations have greatly advanced our understanding of the bi-axial behavior of the carotid artery, necessitating an up-to-date review to summarize and classify the published literature in collaboration with technical and clinical experts in the field. Within this review, the state-of-the-art methodologies for carotid wall motion estimation are described, and the observed relationships between longitudinal motion-derived indices and vascular health are reported. The vast number of studies describing the longitudinal motion pattern in plaque-free arteries, with its putative application to cardiovascular disease prediction, point to the need for characterizing the added value and applicability of longitudinal motion beyond established biomarkers. To this aim, the main purpose of this review was to provide a strong base of theoretical knowledge, together with a curated set of practical guidelines and recommendations for longitudinal motion estimation in patients, to foster future discoveries in the field, toward the integration of longitudinal motion in basic science as well as clinical practice.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Arteriosclerosis; Atherosclerosis; Block matching; Cardiovascular risk factors; Carotid artery; Longitudinal motion; Motion estimation; Speckle tracking; Ultrasound; Vascular health